Mitochondrial diseases and ATPase defects of nuclear origin - Houštěk, Josef; Mráček, Tomáš; Vojtíšková, Alena; Zeman, Jiří (Biochimica et biophysica acta, 2004)
Dysfunctions of the F(1)F(o)-ATPase complex cause severe mitochondrial diseases affecting primarily the paediatric population. While in the maternally inherited ATPase defects due to mtDNA mutations in the ATP6 gene the enzyme is structurally and functionally modified, in ATPase defects of nuclear origin mitochondria contain a decreased amount of otherwise normal enzyme. In this case biosynthesis of ATPase is down-regulated due to a block at the early stage of enzyme assembly-formation of the F(1) catalytic part. The pathogenetic mechanism implicates dysfunction of Atp12 or other F(1)-specific assembly factors. For cellular energetics, however, the negative consequences may be quite similar irrespective of whether the ATPase dysfunction is of mitochondrial or nuclear origin.
Keywords: mutace; Animals; mitochondriální nemoci; Mitochondria; DNA, Mitochondrial; Fibroblasts; Vacuolar Proton-Translocating ATPases; lidé; Cell Nucleus; Reactive Oxygen Species; adenosintrifosfatasy; Mutation; fibroblasty; Mitochondrial Diseases; mitochondrie; buněčné jádro; Mitochondrial Proton-Translocating ATPases; mitochondriální DNA; reaktivní formy kyslíku; mitochondriální protonové ATPasy; vakuolární protonové ATPasy; zvířata; Adenosine Triphosphatases; Humans